Experimentações curriculares e juventudes em redes conexionistas e inventivas na contemporaneidade - Andrade, Roger Vital França de (2015)
This research investigates the entanglements experienced by young peoples in their wanderings through the contemporary curricular timespaces in their conexionist and inventive processes, and weaves a narrative presenting how these young peoples experience the flows of a Body without Organs with and in spite of capitalism. Aiming at composing other nets with theoretical productions that permeate the problematic field, 180 works available at the database of the Digital Library of Thesis and Dissertations of the Brazilian Institute for Information in Science and Technology, relative to the years from 2012 and to 2014 have been analyzed, taking the following descriptors as analyses nets: bodies and curriculums; subjectivities and contemporaneity; nets and learnings. The methodological journey took place in the very movement curricular/life in the company of the incarnated young peoples at their experiences and learnings, which have expressed themselves and gained visibility through the net of conversations that have been used to produce data. This movement had its origin in the research field, which was an Elementary School in the municipality of Serra in the Espírito Santo State, that allowed the fabrication of a narrative registered in a field diary considering its virtualities, truth productions, fragmented stories and its non-linearities. Amidst its theoretical intercessors, the contributions of Canevacci (2000, 2005), Carvalho (2009, 2011, 2012), Deleuze (1991, 1997, 2007), Deleuze and Parnet (2004), Deleuze and Guattari (1995, 1996), Foucault (1986, 1996, 1997, 2002, 2010), Hardt and Negri (2006, 2010), Larrosa (2002, 2010, 2012), Parente (2010, 2013), Pelbart (2011) and Santaella (2004) stand out. It bets and nourishes hopes that, in the functioning, in the experimentations and entanglements exercised on a daily basis by young peoples throughout conexionist nets, inventive and others, which have not been named yet – while they establish synapses with other bodies, affections, machines, languages and desires promoted by the flow of a Body without Organs –, the young peoples would be filling plural curricular timespaces in expansive and inaugural mode, spreading out as inventive learnings that happen in the midst of the encounters of these bodies in constant deterritorialization flows.